AComparative Qualitative and Quantitative Study of Anthraquinone Derivatives in the Roots of Rheum ribes and Rheum emodi by HPLC - Alaadin M. Naqishbandi; Anna K. JÃ¤ger; Ekbal H. Al-Khateeb (College of Pharmacy University of Baghdad, 2017)
High performance liquid chromatography was applied for the separation and identification of four antharquinone derivatives, aloe emodin, emodin, chrysophanol and physcion. The separation was carried out using Eurospher 100, C18 column (4.6 mm i.d. x 250 mm, 5 Âµm) under the following conditions: acetonitile (solvent A) and water: acetic acid (99.9: 0.1 v/v, pH 3.5)( solvent B) as a mobile phase with isocratic elution with 30% solvent B at flow rate 0.8 ml/min. The detection wavelength was set at 254 nm. The four antharquinone derivatives were isolated from the Iraqi rhubarb, Rheum ribes root by preparative TLC, their structures were identified by 1H NMR and used as standards for HPLC analysis. The percentages of aloe emodin, emodin, chrysophanol and physcion in rheum ribes root were 0.39%, 0.014%, 0.089%, and 0.072%, respectively. While for Rheum emodi root, only the first three anthraquinone derivatives were identified and their percentages were 0.48%, 0.32% and 1.56%, respectively. The method was found to be reproducible and convenient for qualitative and quantitative analysis of anthraquinone derivatives. Keywords: Rheum ribes, Rheum emodi, Anthraquinone, HPLC